Hubungan kadar TNF-Î± dengan HOMA-IR pada pasien diabetes mellitus tipe-2 di Rumah Sakit Umum Pusat Haji Adam Malik, Medan, Indonesia - Poltak Poltak; Santi Syafril; Ratna Akbari Ganie (DiscoverSys Inc., 2019)
Background: The homeostatic assessment (HOMA) of the first cell-Î² (B) and insulin (IR) function is used to determine insulin sensitivity and cell-Î² function of insulin plasma concentrations and fasting glucose. High extracellular glucose levels will trigger an increase in ROS production (which in turn will increase the formation of Reactive Oxygen Species) expression of TNF Î± (Tumor Necrosis Factor-Î±) and exacerbate oxidative stress. The study aimed to determine the relationship between TNF Î± and HOMA-IR in type 2 DM.Method: A cross sectional study was conducted at the H. Adam Malik General Hospital Medan from December-February 2018 in 43 patients with type 2 DM. Fasting insulin levels were examined using Celuminescence Microparticle Immunoassay and fasting glucose levels with Enzymatic and TNF Î± methods with the Elisa method. The relationship of the characteristics of TNF Î± levels with HOMA-IR in type 2 DM using the Kolmogorov Smirnov test used the Spearman's rank correlation test with SPSS version 20 for windows.Results: The total sample was 43 samples of patients with type 2 diabetes mellitus. Most of the respondents were male (62.8%) and had a median age of 57 (39-87) years. In this study, the TNF-alpha levels were 87.28 (18.43-846.05) pg/ml. While the HOMA-IR level was 3.36 (0.41-25.82). There was no significant correlation between serum TNF Î± levels and HOMA-IR in type 2 DM patients (P> 0.05).Conclusion: There is no significant relationship between TNF Î± levels and HOMA-IR in type 2 DM patients.